Patterns of use and survival outcomes of positron emission tomography for initial staging in elderly follicular lymphoma patients. Issue 7 (3rd July 2017) - Rai, Ashish; Nastoupil, Loretta J.; Williams, Jessica N.; Lipscomb, Joseph; Ward, Kevin C.; Howard, David H.; Lee, Daniel; Flowers, Christopher R.
Abstract: The role of positron emission tomography (PET) in the initial assessment of follicular lymphoma (FL) has been a topic of debate. We examined the patterns of utilization of PET staging in FL and assessed the association of PET with survival. Using the SEER-Medicare database, we identified 5712 patients diagnosed with first primary FL between 2000 and 2009. Older age, African–American race, poor performance status, B-symptoms and history of anemia were negatively associated with PET staging. Receipt of PET staging was positively associated with treatment at institutions affiliated with research networks and with residence in areas with higher concentrations of nuclear medicine specialists. PET was associated with improved lymphoma-related (HR 0.69, 95% CI: 0.58–0.82) and overall (HR 0.75, 95% CI: 0.68–0.83) survival. Our findings substantiate the use of PET as the standard of care for imaging in FL patients. Further investigation is warranted to identify mechanisms underlying the apparent survival advantage associated with PET staging in FL.